2011
DOI: 10.1093/hmg/ddq558
|View full text |Cite
|
Sign up to set email alerts
|

SOX9 controls epithelial branching by activating RET effector genes during kidney development

Abstract: Congenital abnormalities of the kidney and urinary tract are some of the most common defects detected in the unborn child. Kidney growth is controlled by the GDNF/RET signalling pathway, but the molecular events required for the activation of RET downstream targets are still poorly understood. Here we show that SOX9, a gene involved in campomelic dysplasia (CD) in humans, together with its close homologue SOX8, plays an essential role in RET signalling. Expression of SOX9 can be found from the earliest stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 42 publications
3
89
1
Order By: Relevance
“…Sox9 belongs to SOX group E (SoxE), along with Sox8 and Sox10 (Foster et al, 1994). Sox9 has important functions in the development of several organs, including the liver, pancreas, lung and kidney (Furuyama et al, 2011;Reginensi et al, 2011;Seymour et al, 2012;Chang et al, 2013;Rockich et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Sox9 belongs to SOX group E (SoxE), along with Sox8 and Sox10 (Foster et al, 1994). Sox9 has important functions in the development of several organs, including the liver, pancreas, lung and kidney (Furuyama et al, 2011;Reginensi et al, 2011;Seymour et al, 2012;Chang et al, 2013;Rockich et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One intriguing candidate is Sox9, which is highly expressed in distal epithelial cells undergoing active branching (21) (Fig. 3) and required for the development of two other branched organs, the kidney and the pancreas (34,35). To test the role of Sox9 in mouse lung development, we deleted it specifically in the epithelium with a Shh Cre allele (16,17).…”
Section: Negative Correlations Between Branching Morphogenesis and Almentioning
confidence: 99%
“…It has been reported that Pou3f3 (Nakai et al, 2003), Dll1 (Kobayashi et al, 2008b), Sox9 (Reginensi et al, 2011), Dkk1, Papss2, Greb1, Pcsk9, Lhx1 and Bmp2 (Georgas et al, 2009) are expressed specifically in the distal RV, whereas Cdh6 (Cho et al, 1998), Wt1 and Tmem100 (Georgas et al, 2009) are expressed in the proximal RV. In addition, Ccnd1, Jag1, Ccdc86 and Wnt4 were reported to be expressed throughout the RV, but with higher expression in distal than proximal regions (Georgas et al, 2009).…”
Section: Single Cell Analysis Of the Renal Vesiclementioning
confidence: 99%